Microstructural influence on tolerance to corrosion-induced damage in hardmetals. (5th December 2016) - Tarragó, J.M.; Fargas, G.; Isern, L.; Dorvlo, S.; Tarres, E.; Müller, C.M.; Jiménez-Piqué, E.; Llanes, L.
Abstract: The influence of the microstructure on the tolerance of WC-Co cemented carbides to corrosion damage was studied by using residual strength as the critical design parameter. In doing so, samples were immersed in synthetic mine water solution for different times, and changes induced by corrosion exposure were assessed. A detailed 3D FIB/FESEM tomography characterization of corrosion damage-microstructure interactions is included. Results reveal that corrosion damage may result in relevant strength degradation on the basis of stress rising effects associated with the formation of surface corrosion pits. Thus, as immersion time increases strength gradually decreases. Fractographic examination reveals the formation of semi-elliptical and sharp corrosion pits for studied medium- and ultrafine-sized cemented carbides, respectively. The latter has a much more pronounced stress rising effect, and consequently higher strength losses were determined for ultrafine grades. Corrosion process consists of a selective attack of the binder that is dissolved in the corrosive media. Initially, it is located at centres of binder pools and as exposure time in the media increases, corrosion evolves consuming the rest of the pools which finally leaves an unsupported WC grain skeleton at the surface. Graphical abstract: Highlights: Stress raising effects due to corrosion damage may result in relevant strength loss. Carbide mean grain size strongly influences corrosion pits geometry. Higher damage tolerance to corrosion when rising the carbide mean grain size. A description of corrosion process is provided by means of 3D FIB/FESEM tomography.